Chapter 1 FAIL! Are We Headed towards Critical Failure Studies? - Mica, Adriana (Taylor & Francis, 2023)
The chapter outlines the scope and structure of the Routledge International Handbook of Failure. It makes a point about the tendency in recent works on failure to advance critical rhetoric and provides a genealogical scrutiny that goes beyond the episodic materialization of failure, that is, failure as an event. This analysis further aims to reveal the complexity of relations, institutions and understandings that constitute regimes and cultures of failure. The chapter signals the main dimensions targeted and unraveled in this new research on failure: inequality, invisibility, power, the future, re-imagining of neoliberal logics of success, and failure alternatives. It also allows readers to grasp the critical and analytical synergy in critical failure studies, both ongoing and planned, which approach the subject from a variety of disciplines, such as sociology, anthropology, International Relations and development research, public policy, organization and management studies, Science, Technology and Society (STS), queer theory, disability studies, performance studies, narrative analysis and cultural theory.